2018
DOI: 10.1186/s12879-018-3575-x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, risk factors and outcomes of early bloodstream infection in patients with malignant hematologic disease after unrelated cord blood transplantation: a retrospective study

Abstract: BackgroundBloodstream infection (BSI) is one of the major causes of morbidity and mortality for patients undergoing hematopoietic stem cell transplantation (HSCT). The unrelated cord blood transplantation (UCBT) can provided opportunities for patients without suitable donors for bone marrow transplantation (BMT) and peripheral blood stem cell transplantation (PBSCT), while few studies have addressed BSI after UCBT. The aim of this study was to analyse the incidence and risk factors of BSI, causative organisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
6
14
0
4
Order By: Relevance
“…Peripheral blood combined with bone marrow transplantation, hematopoietic implantation is relatively fast, which may be the reason for the lower incidence of BSIs in this group of patients, relative to peripheral blood and cord blood transplantation. 31–33 …”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood combined with bone marrow transplantation, hematopoietic implantation is relatively fast, which may be the reason for the lower incidence of BSIs in this group of patients, relative to peripheral blood and cord blood transplantation. 31–33 …”
Section: Discussionmentioning
confidence: 99%
“…This incidence is comparable to other pediatric and adult cohorts, with cumulative incidences in pediatric cohorts ranging broadly from 15% to 65% [ 1 , 4 , 19–22 ]. Previous studies reported an increase in BSI in association with specific risk factors, including allogeneic HSCT, unrelated HSCT donor, myeloablative conditioning, total body irradiation, and delayed engraftment [ 1 , 20 , 23–25 ]. Although we did not directly assess the contribution of these factors to the risk of BSI, our cohort is a unique population that has a high prevalence of several of these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug-resistant (MDR) Enterobacteriaceae, including extended-spectrum β-lactamase (ESBL) bacteria and carbapenem-resistant Enterobacteriaceae (CRE), is a great threat to recipients in HSCT [1]. BSI caused by multidrug-resistant Gram-negative bacteria (MDR-GNB) after transplantation, mostly including Escherichia coli and Klebsiella pneumoniae [2], has shown a negative impact on long-term survival in transplantation [3]. Herein, we present four cases in which CRE was detected in neutropenic patients with hematologic malignancies and focus on the treatment of MDR bacteria.…”
Section: Introductionmentioning
confidence: 99%